Outbreak of SARS-CoV-2 B.1.617.2 (delta) variant in a nursing home 28 weeks after two doses of mRNA anti-COVID-19 vaccines: evidence of a waning immunity. (April 2022) - Pierobon, Alice; Zotto, Alessandra Dal; Antico, Antonio; De Antoni, Mario Ernesto; Vianello, Liviano; Gennari, Monica; Di Caprio, Antonio; Russo, Francesca; Brambilla, Gianfranco; Saugo, Mario
Abstract: Objectives: To describe a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) B.1.617.2 (Delta) variant outbreak among residents ( n = 69) and health workers ( n = 69) of a small nursing home in northeastern Italy, with full vaccination coverage of 91% and 82%, respectively. Evaluation of the anti-Spike IgG titres 28 weeks after the mRNA vaccine booster dose against SARS-CoV-2 infection and severe coronavirus disease 2019 (COVID-19). Materials and methods: Sera were collected within 48 hours from the index case; anti-Spike IgG was determined (expressed as WHO binding antibody units (BAU)/mL) through a commercial quantitative assay; SARS-CoV-2 was diagnosed using RT-PCR, and full-genome sequencing was performed for lineage characterization. Residents were grouped according to anti-Spike IgG titres (≤50, 51–1000 and > 1000 BAU/mL) and the resulting protection against infection and severe disease was measured. Results: None of the health workers and 14 of the 59 (24%) residents fully vaccinated and without a previous SARS-CoV-2 infection showed anti-Spike IgG ≤50 BAU/mL (one-sided Fisher exact test, p 0.011). Among these residents, a level of anti-Spike IgG ≤50 BAU/mL resulted in a higher risk of SARS-CoV-2 infection (relative risk 1.55, 95% CI 1.17–2.05) and severe COVID-19 (relative risk 5.33, 95% CI 1.83–15.57). Conclusion: Low levels of SARS-CoV-2 neutralizing anti-Spike IgG in serum 28 weeks after the administration of the second dose parallel the waning of vaccine protection.